Metode Resitasi sebagai stimulus Kemandirian Belajar Peserta Didik Dalam Pembelajaran Sejarah Kebudayaan Islam. - MAMLUAH, AYA; Ulva Badi’ Rohmawati; Wahyu Muqorrobin (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2024)
This research aims to explore the implemention of the recitation methodas a stimulus to enhance students' self-directed learning in the teaching of IslamicCultural History. The recitation method involves assigning tasks to students,which are then completed outside the classroom, and the results are presentedin the form of presentations or reports. This research adopts a qualitativeapproach, utilizing interviews, observations, and document analysis as datacollection techniques. The findings indicate that the recitation method is effectivein stimulating students' self-directed learning, reinforcing understanding of thematerial, and enhancing interaction in the learning process. The implications ofthis research may contribute to the development of teaching strategies that aremore oriented toward students' self-directed learning in the field of IslamicCultural History.